State Savings Banks in Lithuania in the Early 20th Century - Jasienė, Meilė (Ekonomika, 2008)
The paper attempts to reconstruct the picture of the state savings bank system and its structure in Lithuanian governorates in the beginning of the 20th century. The same economic, political, social contradictions as in the whole credit system of the lagging behind Russian Empire as compared with Western European states were typical in the creation and activity of savings banks. Among other means (accumulation of land in the hands of Russians, colonial policy of taxes and customs), discriminative credit policies were used. The formation of credit resources using savings of the occupied countries also served for the imperial purposes of Russia. The opening and activities of savings banks were regulated by special statutes in which the objective of savings banks was indicated: to provide the possibility for poor people to accumulate funds in small amounts and get interest for them. However, the operations of savings banks were trivial, they managed to accumulate only very small amounts of money. In 1895, the new Statute of savings banks was approved and they were called State Savings Banks. The State Bank of Russia headed over the savings banks. According to the new Statute, the order of the opening of savings banks was easier. It became possible to open state savings banks and their branches in all cities and settlements - at the State Bank, treasuries, customs, at all governmental and public offices, private offices and enterprises. The spread of the network of savings banks became easier, deposits grew up. Deposits in saving banks in the period 1899-1913 increased rather rapidly: in the Vilnius govemorate 2.9, in Kaunas 2.6, and in Suvalkai 3.1 times. The number of savings banks in Lithuanian governorates in this period increased 1.45 times. At the beginning of 1913, in Lithuanian governorates operated 29 central savings banks and one city branch, 241 savings banks at post offices, 11 at railway stations, and 2 saving banks in factories. The number of all types of savings banks was biggest in Šiauliai district (22), Vilnius and Raseiniai districts (21 in each), and the smallest in Naumiestis district (4). The biggest amount of deposits in total, its average per one savings bank, and the average amount of passbooks per one saving bank was in the Vllnius governorate and the smallest in the Suvalkai governorate. The average biggest amount of passbooks in savings banks per one thousand inhabitants was in the Vllnius governorate and the smallest in the Suvalkai governorate, too. Savings banks’ deposit funds were invested in state bonds. Formation of the credit resources of the Russian Empire using savings of people of the occupied countries was one of the means of the realization of Russia’s colonial policy. The Lithuanian deposit funds brought away from Lithuania have never been returned.